1991
DOI: 10.1093/carcin/12.12.2221
|View full text |Cite
|
Sign up to set email alerts
|

Loss of glutathione S-transferases in pollution-associated liver neoplasms in thite suckers (Catostomus commerson) from Lake Ontario

Abstract: White suckers (Catostomus commersoni) are one of two species of bottom-feeding fish in which various liver neoplasms are more prevalent in urban/industrial sites in western Lake Ontario than in less polluted sites in the Great Lakes. Previous studies indicate that white suckers excrete metabolites of various polycyclic aromatic hydrocarbons (PAHs) in bile, and that glutathione transferase (GST)-mediated conjugation is a major detoxification pathway for the PAH benzo[alpha]pyrene. To determine whether hepatocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In contrast to rodents exposed to some mutagenic carcinogens (200), GST was deficient in FCA and hepatic neoplasms in white suckers exposed to PAH-contaminated sediments (182). The majority of DMBA and aflatoxin B 1-induced preneoplastic and neoplastic lesions in rainbow trout were also deficient for GST (104), although expression was induced in some FCA.…”
Section: Molecular Markersmentioning
confidence: 83%
“…In contrast to rodents exposed to some mutagenic carcinogens (200), GST was deficient in FCA and hepatic neoplasms in white suckers exposed to PAH-contaminated sediments (182). The majority of DMBA and aflatoxin B 1-induced preneoplastic and neoplastic lesions in rainbow trout were also deficient for GST (104), although expression was induced in some FCA.…”
Section: Molecular Markersmentioning
confidence: 83%
“…Reduced expression of these subunits has been attributed either to dedifferentiation (58) or to differential subunit expression during more rapid cell proliferation (59,60). Also, advanced hepatocellular neoplasms in fish exposed environmentally (19) or experimentally (18) to genotoxic carcinogens are GST deficient. Thus, preexisting or acquired defects in GSTdependent resistance are becoming recognized as an important feature in various neoplastic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the pathogenesis of liver neoplasia have shown that progression of pollution-associated liver neoplasms in fish is associated with a loss of hepatic GST expression, both in white suckers from Lake Ontario and in experimentally induced liver neoplasms in rainbow trout (18,19). We have proposed that this loss of GST-associated resistance might increase the susceptibility of preneoplastic populations of hepatocytes to some unidentified exogenous or endogenous genotoxic substances that are putatively responsible for further DNA damage during malignant progression.…”
Section: -158)mentioning
confidence: 99%
“…These observations suggest that the resistant phenotype of preneoplastic hepatocytes might favor their selective expansion during exposure to the toxic effects of bile acids. GSTs bind and transport bile acids intracellularly, and this binding inhibits GST activity in vitro (5,17,30,39,46,47 (25,41). Also, white suckers from sites where pollution-associated liver neoplasms occur have an inflammatory cholangiohepatitis that substantially reduces hepatic GST activity (24).…”
Section: Introductionmentioning
confidence: 99%
“…Also, white suckers from sites where pollution-associated liver neoplasms occur have an inflammatory cholangiohepatitis that substantially reduces hepatic GST activity (24). Accordingly, we have proposed that loss or inhibition of GST activity might favor malignant progression by increasing susceptibility of hepatocytes to genotoxic damage by exogenous or endogenous compounds normally detoxified by these enzymes (25,41 Enzyme activities for 1-chloro-2,4-dinitrobenzene (CDNB) and trans-4-phenyl-3-buten-2-one (tPBO) were determined at 25°C (15 (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%